The philosophical values of Rimpu traditional clothing of Bimanese people in West Nusa Tenggara - Irfan Hidayat,; Iswahyudi, Iswahyudi (Technium Social Sciences Journal, 2022)
This study aims to describe the philosophical value of Rimpu traditional clothing, the culture of Bimanese people in West Nusa Tenggara including (1) the history of the existence of Rimpu, and (2) the function of wearing Rimpu, particularly for the Bimanese people. This research uses a descriptive qualitative method and the instrument in this research is the researcher. To strengthen this research, the researcher employed observation, interview, and documentation as the guideline. The object of this research is the Rimpu tradition in Bima. Data validation was performed using referential adequacy and observational persistence. The data analysis technique employed in this research is descriptive qualitative consisting of several stages of data collection, data presentation, and conclusion. Based on the research results, the philosophical values of Rimpu traditional clothing as the culture of Bimanese people in West Nusa Tenggara are (1) as the regulation for women to cover their ‘awrah emerged after the spread of Islamic teaching in Bima, women started to cover their ‘awrah by wearing a woven sarong called Rimpu, and (2) it functions as a religious identity, combines the local and typical Bimanese culture, protects women when interacting with the opposite sex during the colonial period, and also against a bad environment.